(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the care of patients with neurogenic bladder due to spinal cord injury at the Rehabilitation Center, Bach Mai Hospital in 2022 Subjects and research methods: Describe the research at 4 points (week 1, week 2, week 3, week 4) of patients in the selection criteria with a set of interview questions for patients to evaluate care activities through 9 criteria: skin care, eating care, urinary care, respiratory care, intestinal care, embolism prevention care, correct posture care, movement recovery for patients after surgery, counseling care for patients.Analyze the data on SPSS 16.0 with a table describing the frequency and ratio. Results: Results of urinary care activities include: hygiene ≤ 1 time/day accounting for 21.8%, urinary rehabilitation > 1 time/day accounting for 98.5%; activities of eating care, respiratory care, intestinal care, skin care, preventive care of embolism, correct posture care and physical training at 4 times without change are: 86.5%, 87.3%, 96.1%, 98.5%, 99.3%, 100%, 100%; Health education counseling care activities range from 97.7 to 98.5%, respectively. 82% of patients have good care results; 18% of care results are not good. Conclusions: Results of care activities ranged from 82.4% to 100%; good care results accounted for 82%.